A Historical Perspective. Issue 6 (1st November 2006) - Neal, Joseph M.; Baker, Jeff
Abstract : Regional Anesthesia and Pain Medicine celebrates its 30th anniversary in 2006. What began as a 10-page, industry-sponsored bulletin has evolved into a major anesthesiology and pain journal. This history article chronicles the journal's growth and development over 3 decades.